The Effect of Group Work on Expressive-Artistic Activities for the Emotional Regulation of University Students - Lilyan Vega-Ramírez; Andreea Vidaci; Christian Hederich-Martínez (MDPI AG, 2022)
The purpose of higher education is the development of basic and professional skills to prepare students for the following stages of life. Social abilities and emotional regulation are considered to be part of these skills and could be improved through a group-work method. The aim of this study is to describe the emotional regulation process perceived by university students after group work is realised in expressive-artistic activities. The 69 participants (28 women and 41 men) aged between 19 and 26 (mean age 20.5, SD 2.1) were all second-year students of a Physical Activity and Sport Science degree. The data were collected through the questionnaire AIRE (Adaptative Instrument for Regulation of Emotions) applied by online form. The results revealed that the main goal of the students was to enjoy and have fun during the group work and gain new ideas from their peers. The biggest struggle was the schedule because some of them presented other personal or family commitments that limited their availability to practice. Overall, most of the participants affirmed that there are completely satisfied with the group project. In conclusion, group work within expressive-artistic activities improves social interaction and social skills but could be influenced by external factors (family, work, and other social commitments).